The Effect of Job Stress and Emotional Labour on Customer Satisfaction and Sales Performance: A Research on Medical Representatives (Third Sector Social Economic Review, 2025)
This study was conducted to examine the effects of job stress and emotional labour levels of medical sales representatives working in the pharmaceutical industry on their sales performance and customer satisfaction. Using quantitative research methods, data collected from participants were analysed through statistical techniques. The findings reveal that emotional labour processes play a significant role in shaping job stress, sales performance, and customer satisfaction. Emotional labour was examined in three dimensions surface acting, deep acting, and natural emotions—and it was determined that surface acting is the primary factor increasing job stress. Deep acting also elevates stress levels, whereas natural emotions do not have a meaningful effect on stress. However, the influence of emotional labour on sales performance exhibits a different pattern: both deep acting and natural emotions enhance sales performance, while surface acting shows no significant impact. Regarding customer satisfaction, only natural emotions were found to have a positive effect, indicating that customers easily perceive authenticity and that genuine emotional expression plays a critical role in satisfaction. Additionally, job stress was not found to influence sales performance, whereas sales performance significantly increased customer satisfaction. Overall, the findings underline that emotional labour processes of medical representatives constitute a strategic organisational component that must be supported at the corporate level.
Keywords: Medical Representetive; Emotional Labour; Job Stress; Sales Performance; Customer Satisfaction